BENIH POLIEMBRIO PADA TANAMAN KOKOSAN DAN JERUK - Renan Subantoro; Rossi Prabowo (Universitas Wahid Hasyim, 2012)
Polyembryonic is an embryo that has the tendency of more than one embryo in the seed (derived from the ovules), although this embryo extra does not have ripe embryos. The goal this study was to determine poliembrio on the citrus and kokosan, find out the growth of the seed sprouts from orange and kokosan poliembrio seeds and find out if the seeds can be used as seed. The materials used in this experiment include citrus and kokosan seed and medium sand. The tools used are cotton, filter paper, and the germination tub pinset. The experiment using factorial experimental design 2 X 4 (2 faktor) were arranged in a completely randomized design (CRD) for experiments conducted in the laboratory. The first factor is the separation of the embryo consists of two separated ways embryos and embryos are not separated. The second factor is the number of embryos composed of 4 cedar is the number of embryos 2, 4, 6 and 8. Conclusion research are citrus and kokosan seed have more than one embryo in the seed (Poliembrio), the growth of sprouts from seed poliembrio influenced by the size of the embryo, food reserves and germination environment, and seeds can be used as seed poliembrio the terms were grown in an optimal environment. Key words : poliembrio, citrus, kokosan , seeds , and sprout